Underpinning rural Bumiputera mompreneurs' work-life balance framework towards sustainable entrepreneurship - Hazudin, Siti Fahazarina; Sabri, Mohamad Fazli; Tengku Sharif, Tengku Intan Suzila; Abd Aziz, Nurul Nadia; Ridzuan, Mohd Rozaimy (Human Resource Management Academic Research Society, 2021)
This paper aims to underpin the Bumiputera women entrepreneurs' (BWEs) sustainable worklife balance framework based on business-family relationships. Aiming to propel holistic success among BWEs in rural society, the study focuses on marital and parenthood balances. The Conversion of Resource Theory (COR) has been adopted to identify the factors contributing to the level of women’s entrepreneurship activities in the context of family relationships from the past empirical studies. This study provides a basis for the starting point in filling the existing gap by discovering BWEs and their families' views on factors that can cause work-life imbalances within a business family relationship. The study's baseline should be directed towards meeting the inclusive socio-economics agenda for an equitable share of the economic resources of disadvantaged minority women and families. The life balances and support needed to be addressed by policymakers so that the economic potential of this group can be fully utilised especially when entrepreneurship is considered a reliable economic weapon to combat poverty for the rural society.